Thermodynamics of calcium binding to heparin: Implications of solvation and water structuring for polysaccharide biofunctions - Brenna M. Knight; Connor M. B. Gallagher; Michael D. Schulz; Kevin J. Edgar; Caylyn D. McNaul; Christina A. McCutchin; Patricia M. Dove (Proceedings of the National Academy of Sciences, 2025)
Heparan sulfates are found in all animal tissues and have essential roles in living systems. This family of biomacromolecules modulates binding to calcium ions (Ca 2+ ) in low free energy reactions that influence biochemical processes from cell signaling and anticoagulant efficacy to biomineralization. Despite their ubiquity, the thermodynamic basis for how heparans and similarly functionalized biomolecules regulate Ca 2+ interactions is not yet established. Using heparosan (Control) and heparins with different positions of sulfate groups, we quantify how SO 3 − and COO − content and SO 3 − position modulate Ca 2+ binding by isothermal titration calorimetry. The free energy of all heparin-Ca 2+ interactions (Δ G rxn ) is dominated by entropic contributions due to favorable water release from polar, hydrophilic groups. Heparin with both sulfate esters ( O -SO 3 − ) and sulfamides ( N -SO 3 − ) has the strongest binding to Ca 2+ compared to heparosan and to heparin with only O -SO 3 − groups (~3X). By linking Ca 2+ binding thermodynamics to measurements of the interfacial energy for calcite (CaCO 3 ) crystallization onto polysaccharides, we show molecule-specific differences in nucleation rate can be explained by differences in water structuring during Ca 2+ interactions. A large entropic term (- T Δ S rxn ) upon Ca 2+ –polysaccharide binding correlates with high interfacial energy to CaCO 3 nucleation. Combining our measurements with literature values indicates many Ca 2+ –polysaccharide interactions have a shared thermodynamic signature. The resulting enthalpy–entropy compensation relationship suggests these interactions are generally dominated by water restructuring involving few conformational changes, distinct from Ca 2+ –protein binding. Our findings quantify the thermodynamic origins of heparin-specific interactions with Ca 2+ and demonstrate the contributions of solvation and functional group position during biomacromolecule-mediated ion regulation.